Unilateral optic nerve aplasia associated with microphthalmos - Stanković-Babić Gordana; Oros Ana; Cekić Sonja; Vujanović Milena; Babić Rade R. (Vojnosanitetski Pregled)
Intraduction. Optic nerve aplasia is a rare developmental anomaly characterised by the congenital absence of the optic nerve, central retinal vessels and retinal ganglion cells that is seen most often in a unilaterally malformed eye. Case report. We reported a girl with a very rare anomaly of the eye, unilateral aplasia of the optic nerve and microphthalmia. We carried out a complete ophthalmological examination, A- and Bscan ultrasonography, magnetic resonance imaging (MRI) of the orbit and brain, pediatrician, neurological examinations and karyotype determination. The examined child was a third child from the third regular pregnancy, born at term (39 GS, BM 3100 g). Family ocular history was negative. The right corneal diameter was 7.5 mm and left 10 mm. On dilated fundus examination, the right eye showed the absence of optic nerve and central retinal vessels. B-scan echography showed a small right globe (axial length 13.80 mm), normal size left globe (axial length 18.30 mm) and the absence of optic nerve on the right eye. Physical and neurological findings and karyotype was normal. MRI of the orbits and brain marked asymmetry of globe size and unilateral absence of the optic nerve. The patient is under the control of a competent ophthalmologist and prosthetic. Conclusion. Further aesthetic and functional development of a young person is the primary goal in tracking this rare congenital optic nerve anomalies in the malformed eye.